The art of ₋w₋a₋r₋ listening : an examination of the New Zealand Defence Force's civil-military coordination in Pacific disaster relief responses : Master of Philosophy in Defence and Security, Massey University, New Zealand - Roddis, Kendra (Massey University, 2019)
As natural disasters have increased in frequency and intensity in the Pacific, so too has the New Zealand Defence Force’s (NZDF’s) involvement in Humanitarian Assistance and Disaster Relief (HADR). This has made effective civil-military coordination crucial, particularly due to the severity and scale of resulting humanitarian needs. Yet despite the Government of New Zealand Government’s (GoNZ’s) publicised intentions to improve the military’s interoperability and HADR capabilities, this study presents the first independent examination of the NZDF’s civil-military coordination in the context of Pacific HADR. Findings were drawn from a comparative analysis of the NZDF’s involvement in the 2015 Tropical Cyclone (TC) Pam response in Vanuatu and the 2016 TC Winston response in Fiji. These report how stakeholders perceived the NZDF’s civil-military coordination efforts, identify the major obstacles to coordination and discuss how these impacted the HADR provided. Data were triangulated from grey literature and sixty-eight interviews with participants from; the NZDF, GoNZ, international and local humanitarian agencies, affected governments and community representatives. Notably, this is the first time feedback on the NZDF has been collated from Pacific Island governments, humanitarians and populations. Substantial similarities emerged when stakeholders’ views of the NZDF’s coordination were compared. Although the majority of interviewees perceived the NZF’s overall civil-military coordination efforts in a positive light, several previously unreported tensions were reported. Obstacles to coordination also had serious negative impacts on HADR, which indicate that stakeholders did not meet the priority needs of affected populations, in either HADR response. A new model was also developed to summarise thesis findings. This explains how variables, such as stakeholder perspectives, obstacles and mechanisms, interact to produce positive or negative outcomes. The diagram can also be used to evaluate past civil-military coordination efforts and anticipate future challenges. This is a significant benefit to stakeholders, as it provides a simple but practical way to analyse and enhance civil-military coordination efforts.
The word "war" in the title is crossed through
Keywords: 440804 Defence studies